Reka bentuk beg bantuan kecemasan multi-fungsi untuk pasukan beruniform di Institut Pengajian Tinggi (IPT) - Mohd Aiman, bin Hamdani (Universiti Malaysia Sarawak (UNIMAS), 2015)
Beg emergency aid is the first event of an accident. It is a means of saving medications and have additional functions and high added value in terms of design. The resulting product combines emergency stretcher device, life jackets and basic medical needs. This product is multi-functional and ergonomic and safety features focused on that income. This product is designed to provide rescue service more efficient and effective.